Theoretical Study of Fair-Trade Sustainable Hatcheries - Sizing for Cameroon and Indonesia - Awono Onana, Charles; Hona, jacques; Valdas, Laurent Charles (Indonesian Green Technology Journal, 2022)
Fair-trade sustainable hatcheries are designed for developing and emerging countries, such as Cameroon and Indonesia respectively so that they can use their often-generous sunshine at the service of harmonious development. These hatcheries are sustainable by their functioning exclusively from solar irradiation and nocturnal radiative emission. They are fair-trade because of their simplicity which allows them to be manufactured by many local professionals. They are developed so that the compensation in thermal losses is ensured by thermosiphon heat transfer loops thermo-regulated by bimetallic strip. These hatcheries are also designed for tropical or equatorial climatic hazards due to fine modeling of physical phenomena which can also be implemented by using a simple computer. An excellent economic return is expected. Keywords: fair-trade sustainable hatchery; thermosiphon; bimetallic regulator; created entropy; liquid water